Rhodolith-forming species of the subfamilies Neogoniolithoideae and Hydrolithoideae (Rhodophyta, Corallinales) from Espírito Santo State, Brazil - Villas-Bôas, Alexandre Biggio; Riosmena-Rodriguez, Rafael; Tâmega, Frederico Tapajós De Souza; Amado-Filho, Gilberto; Maneveldt, Gavin; Figueiredo, Marcia (Phytotaxa, 2015)
The taxonomy of the rhodolith-forming species of non-geniculate coralline algae from the subfamilies Neogoniolithoideae and Hydrolithoideae (Rhodophyta, Corallinales) found from Espírito Santo State, Brazil, was evaluated based on extensive subtidal sampling. A comparative analysis of the Brazilian material to other recently described species lead us to conclude that one relatively well-known species, namely Hydrolithon rupestre, a conferatum species Neogoniolithon cf. brassica-florida and a probably new species of the genus Hydrolithon, are present in the area. All three species can be distinguished by their tetrasporangial or gametangial conceptacle anatomy. This study strengthens the hypothesis that Brazilian rhodolith beds are comparatively more diverse in numbers of rhodolith-forming species than other areas of the world.